2020
DOI: 10.30525/2661-5150/2020-4-9
|View full text |Cite
|
Sign up to set email alerts
|

The Problem of Institutional Trust in Ukraine and Europe: A Comparative Analysis

Abstract: The article presents the results of studying the formation of institutional trust, which will help to clarify and, at the same time, raise questions regarding the determination of the level of trust in state and political institutions in Ukraine and in modern European countries. In the context of the study, the tasks were considered to identify the factors that influence the formation of citizens’ trust in political institutions, namely: the effectiveness of the activities of political institutions; personal e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
1
0
1
Order By: Relevance
“…Nyhan et al's (2014) research demonstrated the potential dangers of loss-framed messages for uptake in sceptical populations by showing how not only were loss-framed messages ineffective in shifting beliefs and vaccination intent, compared to a control and to other messages, they also had the unanticipated consequence of increasing misperceptions about MMR. In the Ukrainian context, this problem could be particularly acute because trust in vaccination as well as national governance and institutions is very low, in comparison to similar European countries (Izha et al, 2020). This means that loss-framed strategies may not only be ineffective but could even be counter-productive.…”
Section: Risk Appraisal: Loss-framed and Gain-framed Messagesmentioning
confidence: 99%
“…Nyhan et al's (2014) research demonstrated the potential dangers of loss-framed messages for uptake in sceptical populations by showing how not only were loss-framed messages ineffective in shifting beliefs and vaccination intent, compared to a control and to other messages, they also had the unanticipated consequence of increasing misperceptions about MMR. In the Ukrainian context, this problem could be particularly acute because trust in vaccination as well as national governance and institutions is very low, in comparison to similar European countries (Izha et al, 2020). This means that loss-framed strategies may not only be ineffective but could even be counter-productive.…”
Section: Risk Appraisal: Loss-framed and Gain-framed Messagesmentioning
confidence: 99%
“…Przeprowadzane w latach 2002-2018 badania wskazują, że na obejmującej 10 pozycji skali (od stwierdzenia" absolutnie nie ufam" do "w pełni ufam") Polacy deklarowali zaufanie na poziomie 3,8 wobec parlamentu, z kolei Ukraińcy wobec analogicznej instytucji deklarowali zaufanie na poziomie 2,6. Średnia dla krajów europejskich, w których prowadzone były badania wynosiła 4,5 28 . Wyniki przeprowadzonego przez CBOS w 2020 roku sondażu wskazują, że największym zaufaniem respondentów cieszyła się organizacja pozarządowa i jednocześnie instytucja pomocowa -Wielka Orkiestra Świątecznej Pomocy (zaufanie wobec niej zadeklarowało 84% respondentów).…”
Section: Migracja Uchodźcza a Zaufanieunclassified